2014
DOI: 10.1111/nhs.12179
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of glycemic control among adults with type 2 diabetes

Abstract: Type 2 diabetes mellitus is a chronic condition, a global concern, and a serious issue in Sri Lanka, where there is little data regarding the influence of dietary control, exercise, and adherence to medication behaviors among adults diabetes. In this cross-sectional, descriptive study, we identified current factors influencing glycemic control and glycemic control behavior among adults with diabetes. A total of 230 people attending diabetes clinics in a tertiary hospital and a primary care institute were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…The adults with type 2 DM who were 100% (OR: 1.87, p = 0.0081) and those who were 90% (OR: 2.02, p = 0.0353) adherent to hypoglycaemic medications had a statistically significant risk of a high HbA1c of >10% (875.5 mmol/mol; Pihau‐Tulo, Parsons, & Hughes, ). Therefore, the prescription of a combination therapy indicated more aggressive treatment of glycaemic control due to deterioration of the disease (Amarasekara, Fongkaew, Wimalasekera, Turale, & Chanprasit, ). Al‐Khawaldeh, Al‐Hassan, and Froelicher () indicated that the use of insulin was a statistically significant predictor of poor glycaemic control (OR: 0.29, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The adults with type 2 DM who were 100% (OR: 1.87, p = 0.0081) and those who were 90% (OR: 2.02, p = 0.0353) adherent to hypoglycaemic medications had a statistically significant risk of a high HbA1c of >10% (875.5 mmol/mol; Pihau‐Tulo, Parsons, & Hughes, ). Therefore, the prescription of a combination therapy indicated more aggressive treatment of glycaemic control due to deterioration of the disease (Amarasekara, Fongkaew, Wimalasekera, Turale, & Chanprasit, ). Al‐Khawaldeh, Al‐Hassan, and Froelicher () indicated that the use of insulin was a statistically significant predictor of poor glycaemic control (OR: 0.29, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Even though this study findings clearly indicate more than half of the participants had good FBS level; the majority of the participants had poor HbA1c value. Results from other studies have also reported poor glycaemic control among adults with T2DM.According to another Sri Lankan study, most participants did not achieve the recommended fasting blood glucose level (<126 mg/dL) [8]. Iranian study also indicated 42.9% did not reach the target FBS level [21].…”
Section: Discussionmentioning
confidence: 98%
“…As there is no cure for diabetes, self-care activities are promising activities in blood sugar control among patients with T2DM. In Sri Lanka, the majority of the adults with T2DM did not involve recommended DM management strategies including restricting refine sugar, regular exercises or checking blood sugar regularly [7] and the majority of adults with T2DM did not achieve desired glycaemic control [8].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis had evidence suggesting that higher consumption of white rice (with a high glycaemic index) may increase the incidence of diabetes in Asian populations. [6] Amarasekera et al reported the glycaemic control of diabetic patients in Sri Lanka to be suboptimal in 2014 [7], which is probably dependent on poor dietary practices.…”
Section: Introductionmentioning
confidence: 99%